Fast and reliable strain characterization of Streptomyces lividans through micro‐scale cultivation. Issue 9 (23rd May 2017) - Koepff, Joachim; Keller, Matthias; Tsolis, Konstantinos C.; Busche, Tobias; Rückert, Christian; Hamed, Mohamed B.; Anné, Jozef; Kalinowski, Joern; Wiechert, Wolfgang; Economou, Anastassios; Oldiges, Marco
ABSTRACT: Filamentous organisms of the genus Streptomyces play an important role in industrial production processes, due to their extensive secondary metabolism variability, as well as their ability to secrete efficiently large amounts of (heterologous) proteins. While genetic engineering tools are available to rapidly build up large strain libraries, the subsequent strain screening and bioprocess development still constitutes a bottleneck. This is due to the lack of reliable parallelized and accelerated cultivation techniques for morphologically challenging organisms. To address this challenge, we developed an integrated cultivation workflow for Streptomyces lividans based on a parallelized shaken 48‐well microtiter‐plate (MTP) cultivation device. In a first step, a feasible pre‐culture method was identified and validated, revealing high comparability in subsequent main cultivations (coefficient of variation of 1.1% for in‐plate replicates and 3.2% between different pre‐cultures). When validating the growth performance in 1 mL MTP cultivation against an established 1, 000 mL lab‐scale cultivation system, highly comparable cultivation patterns were found for online (pH, dissolved oxygen), as well as for offline derived parameters (glucose uptake, cell‐dry‐weight, and pellet size). Additionally, the two cultivation regimes were compared with respect to transcriptional and protein secretion activity of Streptomyces, showing overall good comparability with minor, but well explainable discrepancies, most probably caused by different energy dissipation (shaking vs. stirring) and adaption effects due to different illumination conditions. Embedded within the presented cultivation workflow, the 1 mL MTP‐based parallelized cultivation system seems to be a suitable screening tool for filamentous and industrial relevant organisms like Streptomyces . This can contribute to widen the field of application for these organisms and facilitate screening and early‐stage bioprocess development. Biotechnol. Bioeng. 2017;114: 2011–2022. © 2017 Wiley Periodicals, Inc. Abstract : Enabling parallelized and miniaturized cultivation for filamentous Streptomyces by using a 48‐well microtiter‐plate based cultivation approach. Optimized pre‐culture workflow and main‐culture parameters ensured highly reproducible growth performance. Detailed validation against 1, 000×larger lab‐scale system revealed very high comparability in process parameters, growth morphology, as well as on transcriptomic and secreted protein level.